TELA’AH TERHADAP IMPLEMENTASI METODE PENENTUAN NISAB ZAKAT PROFESI DI KEMENTERIAN AGAMA KABUPATEN BONE, SULAWESI SELATAN - Ismail Ismail; Parman Parman; Adi Maulana Rachman (SYARIAH: Journal of Islamic Law, 2023)
District religion Bone. The purpose of this research is to find out the method of determining the professional zakat nisab at the Ministry of Religion, Kab. Bone then compares the theory of characters, and draws a conclusion that whose opinion has been used. And the next use is to find out how the implementation of the professional zakat nisab method is carried out at the district ministry of religion. Bone. The research in the form of this thesis is a type of qualitative research with a normative approach based on the opinion of the scholars. This study focuses on the method of determining the nisab of professional zakat and its implementation. The subject of this research is the Ministry of Religion, Kab. Bone and the object of this research is the professional zakat nisab method and its implementation. Data analysis in this study used comparative descriptive analysis, comparing the events in the field with the opinions of fiqh experts in terms of zakat. Based on the results of research that has been carried out on the method of determining the professional zakat nisab at the Ministry of Religion, Kab. Bone can find a conclusion that the Ministry of Religion of Bone Regency in determining the nisab of professional zakat, namely the nisab dose is 653 kg of rice with a zakat rate of 2.5% where the method used is to analogize this professional zakat on two things, namely in terms of nisab on zakat. agriculture, so that it is issued when it is received, and on money zakat in terms of the level of zakat. Bone has been transferred to the concept of infaq, by cutting the salaries of employees who are classified as capable voluntarily every month, then from the collected funds it is used to provide assistance to employees of the district ministry of religion. Bone is deemed worthy to receive it, and it is also intended for people who apply for financial assistance to the district ministry of religion office. Bone.